Unraveling the fatigue puzzle: insights into the pathogenesis and management of IBD-related fatigue including the role of the gut-brain axis - Truyens, Marie; Lernout, Hannah; De Vos, Martine; Laukens, Debby; Lobaton, Triana (Frontiers in Medicine, 2024)
A significant percentage of patients with an inflammatory bowel disease (IBD) encounter fatigue which can profoundly diminish patients’ quality of life, particularly during periods of disease remission when gastrointestinal symptoms have receded. Various contributing risk factors have been identified including active inflammation, anemia, psychological, lifestyle and drug-related factors. While addressing these risk factors has been suggested as the initial approach to managing fatigue, a considerable number of patients still experience persisting symptoms, the primary causes of which remain incompletely understood. Recent insights suggest that dysfunction of the gut-brain axis may play a pathogenic role. This review provides an overview of established risk factors for fatigue, alongside emerging perspectives on the role of the gut-brain axis, and potential treatment strategies.